2005
DOI: 10.1007/s10295-005-0232-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of carbon and nitrogen nutrition on the quality, yield and composition of blastospores of the bioinsecticidal fungus Paecilomyces fumosoroseus

Abstract: The impact of growing cultures of Paecilomyces fumosoroseus in liquid media containing four combinations of glucose and casamino acids (8 g l(-1) or 80 g l(-1) glucose, 1.32 g l(-1) or 13.2 g l(-1) casamino acids) was evaluated, based on blastospore production, germination rate, viability after freeze-drying and short-term storage stability. When blastospores were produced using a high casamino acid concentration, blastospore yields and germination rates were significantly higher (13.2-18.5 x 10(7) blastospore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Previously, it has been shown that the age of the culture as well as environmental conditions affect properties ( e.g. viability and cytotoxicity) of fungal spores (Hallsworth & Magan 1996, Cliquet & Jackson 1999, Murtoniemi et al 2003, Cliquet & Jackson 2005). Normally, spores are collected from the whole mycelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it has been shown that the age of the culture as well as environmental conditions affect properties ( e.g. viability and cytotoxicity) of fungal spores (Hallsworth & Magan 1996, Cliquet & Jackson 1999, Murtoniemi et al 2003, Cliquet & Jackson 2005). Normally, spores are collected from the whole mycelium.…”
Section: Discussionmentioning
confidence: 99%
“…This study indicates that variability in spore properties can be reduced by extracting spores from selected parts of the colony. Defined spore properties are of interest for biocontrol applications (Cliquet & Jackson 1999, Cliquet & Jackson 2005) but may also be of interest for starter cultures of fungal fermentations.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the success of microbial biopesticides depends on obtaining the pathogen at competitive prices to permit its mass-production and commercialization (Gao et al, 2007). Production processes for fungal biopesticides must be low-cost, and yield high concentrations of viable, virulent, persistent spores that can be stabilized to provide a product shelf-life of 12~18 months (Cliquet and Jackson, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Reported by several workers that media constituents simply affect the virulence of biocontrol agents against plant pathogens (Cliquet and Jackson, 2005; Nisha and Kalaiselvi, 2016) and its composition plays a significant role in growing fungal mycelia with increased sporulation (Sun and Liu, 2006; Gao et al, 2007). Liu and Chen (2002) reported that fungi can use wide range of substrates as carbon and nitrogen sources.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon-Nitrogen ratio as well as type of sugar in media plays an important role in determining the pathogenicity of the fungus (Vidal et al, 1998; Gao et al, 2007; Zhao et al, 2013; Nisha and Kalaiselvi, 2016). Therefore, nitrogen and carbon sources were screened for the production of bioactive molecule because they may influence the activity of phytopathogens, and enhances antibiotics production in biocontrol strains and contribute to the variability of biocontrol in different soils and also on host crops (Milner et al, 1995; Thomashow and Weller, 1996; Cliquet and Jackson, 2005; Moorthi et al, 2015). …”
Section: Introductionmentioning
confidence: 99%